The performance of animal husbandry extension officers in the perspective of animal breeders for the achievement of transfer of technology of beef cattle feed. (February 2019) - Abdullah, A; Jamila; SL, Veronica; Nurlaelah, S; Rohani, S
Abstract: The objective of this study was to assess the performance of extension officers in the perspective of animal breeders for the achievement of transfer of technology of beef cattle feed in Bulukumba Regency, South Sulawesi Province. Primary data were derived from animal breeders using the questionnaire as the instrument of research as the reference to do the structured interviews, and secondary data were collected from formal written reports. In addition to that, focus group discussion was conducted among animal breeders to gain more information, and in-depth interviews were performed among key informants. The collected data were analyzed and calculated using the descriptive statistics, the methods of summarizing and tabulating data. Results of the study indicated that the performance of animal husbandry extension officers for the dissemination of the extension subjects of livestock feed technology, the extension methods in the form of face to face communication and/or visits, the demonstration methods of livestock feed technology, getting access to information on the subjects of livestock feed technology and empowering the institutions of animal breeders were 39.7%, 43.8%, 13.4%, 35.7% and 50% respectively. In general, it was concluded that the performance of animal husbandry extension officers for the achievement of transfer of technology of beef cattle feed in Bulukumba Regency was at the intermediate category. Therefore, the performance of animal husbandry extension officers in Bulukumba Regency should be continuously improved to more intensively increase beef cattle productivity, income and welfare of animal breeders. The recommendations suggested in this study were the extension services concerning the transfer of technology of beef cattle feed should compliant with the need of animal breeders in the short and long term and the improvement of performance of animal husbandry extension officers could be conducted through training programs.